The Esteros and Manila's Postwar Remaking - Pante, Michael D (Archīum Ateneo, 2019)
The Second World War transformed Manila from the so-called Venice of the East to the Warsaw of Asia. However, historicizing the impact of the war on the city should go beyond the physical devastation it caused. This chapter investigates the long-term effects of the war on Manila’s urban fabric and its environmental repercussions. It focuses on the acute housing shortage and the shift from water- to land-based transport modes. The chapter argues that Manila’s esteros (estuarial creeks) serve as an index of the effects the war had on the city’s ecology. The emergence of estero communities and the consequent environmental costs showed the struggles of low-income Manila residents in facing the uncertainties of the postwar era and uncovered the city’s grossly unequal socioeconomic structure.